2015
DOI: 10.3174/ajnr.a4588
|View full text |Cite
|
Sign up to set email alerts
|

Protrusion of the Infraorbital Nerve into the Maxillary Sinus on CT: Prevalence, Proposed Grading Method, and Suggested Clinical Implications

Abstract: BACKGROUND AND PURPOSE:The infraorbital nerve arises from the maxillary branch of the trigeminal nerve and normally traverses the orbital floor in the infraorbital canal. Sometimes, however, the infraorbital canal protrudes into the maxillary sinus separate from the orbital floor. We systematically studied the prevalence of this variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Chandra and Kennedy [16], Elnil et al [23] and Mailleux et al [47] reported cases of IOC passing through in the maxillary sinus. Ference et al [26] reported this variation in 12.5% of 200 cases, Lantos et al [41] reported it in 10.8% of 500 cases and Yenigun et al [79] reported in 12.3% of 750 cases. In the present study, this variation was found to be 7% of 150 cases (Fig.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 95%
“…Chandra and Kennedy [16], Elnil et al [23] and Mailleux et al [47] reported cases of IOC passing through in the maxillary sinus. Ference et al [26] reported this variation in 12.5% of 200 cases, Lantos et al [41] reported it in 10.8% of 500 cases and Yenigun et al [79] reported in 12.3% of 750 cases. In the present study, this variation was found to be 7% of 150 cases (Fig.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 95%
“…The protrusion was defined when entire circumference of the inferior orbital nerve was noted within the maxillary sinus without touching the walls. 1 The protrusion was always accompanied with a bony septum. The length of the protruding component along with the bony septum was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Different classification system has been proposed for this variant. 1,4,7 The definition and classification system for our study was adopted from the paper published by Lantos et al 1 Acgar et al in their study The definition by Lantos et al has specific measurements for classification and easy to follow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations